Praktik pengasuhan anak usia dini dalam keluarga migran Madura - Hotimah , Hosnol (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
This research discusses the Early Childhood Care Practices in Madura Family at the Polagan Village, Galis District, Pamekasan Regency. This study aims to investigate the practice of early childhood care in the migrant family in Polagan Village, Galis District, Pamekasan Regency, focusing on the impact of the whereabouts of parents who migrates in the childcare process. This research uses qualitative methods with a case study approach. Data were obtained through interviews, observations, and documentation carried out against Madura migrant families, especially parents and child caregivers. Data analysis is carried out inductiveally by emphasizing the meaning behind the observed data. The results show that breakup with parents can stretch an emotional relationship between children and parents, hampering the formation of basic beliefs, and causing problems in their next child personal development. Parenting strategies implemented by the migrant family in dealing with these challenges included using alternative caregivers such as grandparents or close relatives, as well as utilizing communication technology to maintain interaction with children.